Réponses

2013-12-28T20:22:07+01:00
A = (3x-5)²-(3x-5)(x+4)
1) Développer, réduire et ordonner A
(3x-5)²-(3x-5)(x+4)
=9x²-30x+25-(3x²+12x-5x-20)
=9x²-30x+25-3x²-12x+5x+20
=6x²-37x+45.

2) Factoriser A
(3x-5)²-(3x-5)(x+4)
=(3x-5)(3x-5)-(3x-5)(x+4)
=(3x-5)(3x-5-x-4)
=(3x-5)(2x-9)

3) Calculer A pour x = -2
(3*(-2)-5)(2*(-2)-9)
=(-6-5)(-4-9)
=-11*(-13)
=143
2013-12-28T20:28:23+01:00
1) A = (3x-5)²-(3x-5)(x+4)
9x²-30x+25-(3x²+12x-5x-20)=9x²-30x+25-3x²-12x+5x+20=6x²-37x+45

2)
(3x-5)[(3x-5)-(x+4)]=(3x-5)(3x-5-x-4)=(3x-5)(2x-9)

3)
x=-2
6(-2)²-37(-2)+45=24+74+45
A=143